The answer: median
Ok so good luck it’s right
Answer:
(d) The parabola g(x) will open in the same direction of f(x), and the parabola will be wider than f(x).
Step-by-step explanation:
We assume you intend ...
f(x) = equation of a parabola
g(x) = 2/3·f(x)
Multiplying a function by a factor of 2/3 will cause it to be compressed vertically to 2/3 of its original height. When the function is a parabola, this has the effect of making it appear wider than before the compression.
__
The compression factor is positive, so points on the graph remain on the same side of the x-axis. The direction in which the graph opens is not changed.
The attachment shows parabolas that open upward and downward, along with the transformed version.
They were born 2336 years apart.
384+1952=2336
----------------------------------
Define x :
----------------------------------
Let the width be x.
Width = x
Length = 2x + 5 // Length is 5ft longer than twice the width
----------------------------------
Formula for Perimeter :
----------------------------------
Perimeter = 2 (Length + Width)
----------------------------------
Find Width :
----------------------------------
58 = 2 ( 2x + 5 + x) // Substitute Length and Width into formula
58 = 2 (3x + 5) // Combine like terms
58 = 6x + 10 // Apply distributive property
48 = 6x // Take away 10 from both sides
6x = 48 // Switch sides. Make x the subject
x = 8 // Divide by 6 on both sides
----------------------------------
Find Length and Width :
----------------------------------
Width = x = 8 ft
Length = 2x + 5 = 2(8) + 5 = 21 ft
--------------------------------------------------------------------
Answer: The length is 21 ft and the width is 8 ft.
--------------------------------------------------------------------
Answer:
"Vx: if x is a valid argument with true premises then x has a true conclusion"
In a symbol form
Vx ( P(x) ⇒ 2(x) )
Step-by-step explanation:
The Following statement in the form ∀x ______, if _______ then _______ is a valid argument and this because any valid argument with "true premises" has a "true conclusion" as well
we will rewrite this statement in a universal condition statement form
assume x is a valid argument with true premises
then the following holds true
p(x) : x is a valid argument with true premises
q(x) : x has true conclusion
applying universal conditional statement
"Vx, if x is a valid argument with true premises then x has a true conclusion"
In a symbol form
Vx ( P(x) ⇒ 2(x) )